Introducing a gender-neutral pronoun in a natural gender language: the influence of time on attitudes and behavior - Gustafsson Sendén, Marie; Bäck, Emma A.; Lindqvist, Anna (Frontiers in Psychology, 2015)
The implementation of gender fair language is often associated with negative reactions and hostile attack on people who propose a change. This was also the case in Sweden in 2012 when a third gender-neutral pronoun hen was proposed as an addition to the already existing Swedish pronouns for she and he. The pronoun hen can be used both generically, when gender is unknown or irrelevant, and as a transgender pronoun for people who categorize themselves outside the gender dichotomy. In this article we review the process from 2012 to 2015 when hen has been introduced in the Swedish Dictionary. No other language has so far added a third gender-neutral pronoun that actually has reached the broader population of language users, which makes the situation in Sweden unique. We present data on attitudes toward hen during the recent four years and study how time is associated with the attitudes. In 2012 the majority of the Swedish population was negative to the word, but already in 2014 there was a significant shift to more positive attitudes. Time was one of the strongest predictors for attitudes also when other relevant factors were controlled for. Even though to a lesser extent than the attitudes, the actual use of the word has also increased. We conclude that new words challenging the binary gender system evoke hostile and negative reactions, but also that attitudes can normalize rather quickly. This is very positive because it should motivate language amendments and initiatives for gender-fair language although the first responses are negative.